Genetic Variation of Four Mawar Tomato Cultivar (Solanum lycopersicum L.) based on Morphology and Inter Simple Sequence Repeat (ISSR) Markers - Arumingtyas, Estri Laras; Iezzana, Noor Lylia (Biotropika: Journal of Tropical Biology, 2026)
Tomato (Solanum lycopersicum L.) is one important horticultural vegetable species belongs to the Solanaceae family. Mawar tomatoes are known as a type of tomato that is widely used for seasonings or chili sauce because the fruit has a sour taste and juicy texture. Various mawar tomato varieties are widely available in the market, indicating genetic diversity. This study aimed to analyse the genetic diversity of four mawar tomato cultivars based on morphological characteristics and ISSR molecular markers. The samples used were four tomato cultivars of the mawar variety, namely Maleo, Gammara, Amelia, and Cherroky. Morphological observations were conducted based on the IPGRI and UPOV descriptors. For molecular characterisation, DNA was isolated from leaves, followed by amplification using seven ISSR molecular markers. Bothmorphological and molecular data were converted into binary codes and used for dendrogram construction using NTSYSpc 2.11a. The dendrogram based on morphological characteristics showed that the four mawar tomato varieties studied had similarity coefficients ranging from 0.64 to 0.93. Analysis using ISSR molecular markers yielded similarity coefficient values ranging from 0.24 to 0.81. Based on both dendrograms, the Amelia cultivar consistently formed a cluster separate from the other cultivars. This indicates that morphological differences, may be the result of molecular differences. The Amelia cultivar had the most distinct characteristics compared to the other three cultivars.